2018
DOI: 10.1021/acsami.7b16782
|View full text |Cite
|
Sign up to set email alerts
|

Shear-Induced Brittle Failure along Grain Boundaries in Boron Carbide

Abstract: Abstract:The role that grain boundaries (GB) can play on mechanical properties has been studied extensively for metals and alloys. However, for covalent solids such as boron carbide (B 4 C), the role of GB on the inelastic response to applied stresses is not well established. We consider here the unusual ceramic, boron carbide (B 4 C), which is very hard and lightweight but exhibits brittle impact behavior. We used quantum mechanics (QM) simulations to examine the mechanical response in atomistic structures th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
2
21
0
Order By: Relevance
“…For GB2 and GB3 models, only a narrow plastic deformation range (~0.05 shear strain) is observed, indicating a brittle character for larger grain n-B 4 C. The Von-Mises shear strain analysis indicates that the most slipped atoms distribute within the GB regions for all three GB models, suggesting that the In the GB1 model, the atomic strain analysis suggests that a larger portion of pre-disintegrated icosahedra leads to more fractured icosahedra along GBs, resulting in larger plastic deformation region. This is consistent with our QM study on GBs in B 4 C showing that the high energy GB model is more ductile than the low energy GB model[38]. (iii) The maximum shear stress is achieved before failure initiates.…”
supporting
confidence: 91%
“…For GB2 and GB3 models, only a narrow plastic deformation range (~0.05 shear strain) is observed, indicating a brittle character for larger grain n-B 4 C. The Von-Mises shear strain analysis indicates that the most slipped atoms distribute within the GB regions for all three GB models, suggesting that the In the GB1 model, the atomic strain analysis suggests that a larger portion of pre-disintegrated icosahedra leads to more fractured icosahedra along GBs, resulting in larger plastic deformation region. This is consistent with our QM study on GBs in B 4 C showing that the high energy GB model is more ductile than the low energy GB model[38]. (iii) The maximum shear stress is achieved before failure initiates.…”
supporting
confidence: 91%
“…The DFT study of the deformation of this GB for B 4 C was published previously. 28 In contrast to the previous GB model, the number of crystalline layers was increased between the two GB regions to construct a supercell with cell lengths of a=4.27nm, b=4.27nm, and c=8.21nm, leading to 18,240 atoms, as shown in Fig. 5(A).…”
Section: Accepted Articlementioning
confidence: 99%
“…Studies on polycarbosilanederived SiC ceramic 25 and SiC/SiC composite 26,27 have shown that porosity decreases and mechanical properties improve with the increasing number of PIP cycles. Zhu et al 28 show that increasing pyrolysis temperature and the concentration of SiC fillers in polycarbosilane polymer result in improved mechanical properties in two-dimensional Carbon/ SiC (C/SiC) composites fabricated using the PIP process.…”
Section: Quantum Simulationsmentioning
confidence: 99%
“…As discussed by Balakrishnan et al (2007), boron carbide is a well-known ceramic possessing very high hardness (at least 30GPa), low density (2.5g/cm 3 ), stable thermal properties (the melting temperature ≈ 2500 o C) and also a relatively low price. Such properties make boron carbide a material used for wear resilient coatings, body armors and abrasive grids (Yang et al, 2018). However, these various applications of boron carbides are impeded due to abnormally easy shear-induced brittle fracture.…”
Section: Introduction and Scopementioning
confidence: 99%